Pengaruh Kepengurusan Ikmkw Angkatan 2020 Terhadap Perkembangan Organisasi Ikmkw Kecamatan Wringin - Hikmatul Hasanah; Maliatus Syafiah; Mita Permatasari; Ani Qotuz Zuhro’ Fitriana (CV. ITTC INDONESIA, 2023)
This study aims to provide an overview of the next generation regarding IKMKW leadership and management. The research method used in this study is a quantitative method using a questionnaire as a data collection tool. work program well in the 2020 class management year.